Online enquiry and bill payments management system for a local authority - Dube, Yangekile (Midlands State University, 2019)
Plumtree Town Council is an urban local authority located in Plumtree town in Matebeleland South district of Zimbabwe. It is situated 100 km away from the City of Bulawayo along Bulawayo Botswana road and railway line, 10 km from the border. It services local residents, outlying farmers in Bulilima and Mangwe rural districts as well as tourists as it is a border town. Like other local authorities it is under the jurisdiction of the Ministry of Public Construction Rural and Urban Planning having moved recently from the Ministry of Local Government. The purpose of the study was to develop an online bill enquiry and payment management system after seeing that customers had to visit, call the local authority or wait for the monthly statement to be delivered for them to access their bill. With the online enquiry system customers can get access to their bill anywhere, anytime as long as they have internet access. The feasibility of the projected was aided by the fact that most of the hardware, software and technical skills were already available at Plumtree Town council. The system was developed using instruments like Macromedia Dreamweaver, PHP programming language, MY SQL and WAMP applications. The project was completed on time and now Plumtree Town Council and all its stakeholders enjoys the benefits which include convenience for everyone concerned